Isolation and molecular characterization of the histone methyltransferase DOT1L from the soft tick Ornithodoros moubata - Gobl, Julia (Jihočeská univerzita, 2018)
The aim of this thesis was to isolate the histone methyl transferase dot1l from the organism Ornithodoros moubata and to further characterize this enzyme in our model organism.
Isolation and molecular characterization of the histone methyltransferase DOT1L from the soft tick Ornithodoros moubata
Keywords: epigenetics; tick epigenetics; histone methyltransferase; Ornithodoros moubata; DOT1L; epigenetics; tick epigenetics; histone methyltransferase; Ornithodoros moubata; DOT1L